2024
DOI: 10.1111/eva.13657
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of selection in Mulinia lateralis underpinning its rapid adaptation to laboratory conditions

Zujing Yang,
Ang Zhao,
Mingxuan Teng
et al.

Abstract: The dwarf surf clam, Mulinia lateralis, is considered as a model species for bivalves because of its rapid growth and short generation time. Recently, successful breeding of this species for multiple generations in our laboratory revealed its acquisition of adaptive advantages during artificial breeding. In this study, 310 individuals from five different generations were genotyped with 22,196 single nucleotide polymorphisms (SNPs) with the aim of uncovering the genetic basis of their adaptation to laboratory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…Galactose-3-O-sulfotransferase 1 (GAL3ST1), also known as cerebroside sulfotransferase (CST), is involved in spermatogenesis [31]. The GAL3ST1 was found selected in (dwarf surf clam) and associated with male reproduction [32]. By observing GAL3ST1 knockout mice, it was found that males displayed sterility, which resulted from a block in spermatogenesis before the first meiotic division [33].…”
Section: Patterns Of Selection Signaturesmentioning
confidence: 99%
“…Galactose-3-O-sulfotransferase 1 (GAL3ST1), also known as cerebroside sulfotransferase (CST), is involved in spermatogenesis [31]. The GAL3ST1 was found selected in (dwarf surf clam) and associated with male reproduction [32]. By observing GAL3ST1 knockout mice, it was found that males displayed sterility, which resulted from a block in spermatogenesis before the first meiotic division [33].…”
Section: Patterns Of Selection Signaturesmentioning
confidence: 99%